Understanding the physics of perovskite solar cells for stable and efficient multijunction photovoltaics - Thiesbrummel, J (2023)
Over the past decade, metal halide perovskites have significantly stirred up the field of photovoltaic research. Despite the remarkable increase in efficiency, there is still a lack of comprehensive understanding regarding the device physics and stability of perovskite solar cells. This is problematic because to unlock the full potential of perovskite solar cells and push them towards commercialisation, it is imperative that researchers understand the physical underlying mechanisms that determine whether a solar cell can reliably operate at high efficiency levels over long timescales. This thesis, therefore, concentrates on gaining a better understanding of the device physics and stability of perovskite solar cells, with specific emphasis on two aspects: investigating the effect of mobile ions on the performance and stability of these devices, and understanding performance losses in perovskite-based tandems.